Design and analysis of an active daylight harvesting system for building. (August 2019) - Li, Xiujie; Wei, Yeyan; Zhang, Junbin; Jin, Peng
Abstract: A daylight harvesting system is to guide and distribute sunlight into the building where natural lighting is limited. An effective daylight harvesting system can reduce the electrical load, increase visual comfort and offer numerous health benefits. In this paper, we systematically analysis a new active daylight harvesting system (ADHS) with tracking, solar concentration, collimation and beam alignment. Through a novel four-mirror active tracking, a near collimated solar ray at 100 suns will pass through the light pipe deep into the building from sunrise to sunset. A 0.1 m diameter light pipe can transmit an average of 30, 000 lumen natural light over 8 h per day at Shenzhen, China. With only 2.56% light extraction from the light pipe, a dummy room receives an even illumination with average value of 120 lux without over lighting and glare. The ADHS uses a high-pass mirror to filter out the unwanted infrared radiation, which is the heating load for HVAC. In addition, the effects of slope error, tracking error, incident light angle and solar divergence angle are thoroughly studied by ray tracing. The field test shows that the effective lighting time for an ADHS is more than doubled that of a non-tracking tubular system, and more 100 times increase in transmitted light flux. Other benefits of ADHS are the stability of beam pattern across all solar elevations and the ease of light extraction and control. The ADHS can be widely used in retrofit and new construction due to its robustness and low cost of ownership. Highlights: A daylight harvesting system with active tracking is successfully designed and tested. It can effectively concentrate, collimate and distribute sun light deep into the building. It reduces lighting power consumption and HVAC load. The natural light can be distributed at various locations, and offer numerous health benefits.